2002
DOI: 10.1038/sj.onc.1205553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human lung cancer growth following adenovirus-mediated mda-7 gene expression in vivo

Abstract: Overexpression of the melanoma di erentiation associated gene-7 (mda-7) in vitro results in suppression of lung cancer cell proliferation. However, the ability of MDA-7 to suppress lung cancer in vivo has not been previously demonstrated. In this study, we investigated the possibility of inducing overexpression of the mda-7 gene in human non-small cell lung carcinoma cells in vivo and its e ects on tumor growth. Adenovirus-mediated overexpression of MDA-7 in p53-wild-type A549 and p53-null H1299 subcutaneous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
177
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(187 citation statements)
references
References 15 publications
9
177
0
1
Order By: Relevance
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 80%
“…Ad-mda7 and Herceptin in Her-2 þ breast cancer D Bocangel et al Enhancement of apoptosis in Her-2 þ cells in vitro using a combination of Ad-mda7 and Herceptin We have previously shown that Ad-mda7 is able to rapidly induce apoptosis in various cancer cell lines, cell death being evident as early as 12 h post-transduction. 18,22,24 Here we evaluated the cytotoxic effects of Herceptin in breast cancer cells, using Annexin V staining, as a single agent and in combination with Ad-mda7. Treatment with Herceptin induced low-level apoptosis in Her-2 þ but not in Her-2À cells (Figure 2b).…”
Section: Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 It was reported that Ad-IL-24 could upregulate the expression of TRAIL in both H1299 and A549 tumor cells but not in normal cells. 8 But no further evidence was available. In this article, we reported that ZD55-IL-24 could obviously induce TRAIL expression as shown in Figure 2a, and both ZD55-IL-24 and its combination with ZD55-TRAIL could induce expression of the apoptotic death receptor DR4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that IL-24 can induce apoptosis at multiple levels by activating caspase cascade and upregulating P53, Bax, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and growth arrest and DNA damage protein family genes. [6][7][8] Additional mechanisms for IL-24-mediated cell killing have revealed its regulation of inducible nitric oxide synthase and mitogen-activated protein kinase in melanoma and JUN kinase, b-catenin, phosphatidylinositol 3 0 -kinase and double-stranded RNA-dependent protein kinase in lung and breast tumor cells. [9][10][11][12][13] Thus, IL-24 exerts its tumor-suppressive effects via different signaling pathways in different tumor types.…”
Section: Introductionmentioning
confidence: 99%